Peningkatan Minat dan Bakat dalam Kegiatan Olahraga Padang Loang Cup - Jusman, Jusman; Wati, A Hikmah; ridwan, madinatul munawwarah; Rakhmadhani, Aulia; Ashri, Nur Fadhilah; Ramadhani, Indah Saputri; Asmiah, Asmiah; Syaswan, Muhammad; Adhim, fauzil (LESTARI : Jurnal Pengabdian Kepada Masyarakat, 2024)
Sport is a form of physical and psychological activity, which involves body movement. The Padang Loang Cup is a forum for the sports interests and talents of the people of Padang Loang Village. The aim is as an event to increase the sense of kinship, friendship and cohesiveness between the community and students of KKN UIN Alauddin Makassar posko 11 wave 74, in Padang Loang Village. The results of the Padang Loang Cup competition won the overall winner, namely Palita Hamlet.